Primary plasma cell leukaemia - Md Noor, Sabariah; Lai, Mei I.; Seman, Zainina; Mohd Tohit, Eusni Rahayu; Idris, Faridah; Zulkifli, Noor Fadzillah; Othman, Ainoon (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Plasma cell leukemia (PCL) is a rare form of malignant plasma cell dyscrasia. It can occur as a primary form without prior evidence of multiple myeloma or as a secondary form which is a terminal event in multiple myeloma. It is characterised by a proliferation of plasma cells in blood and the bone marrow. The outcome of plasma cell leukemia is poor with conventional therapy. Here we illustrate a case of primary plasma cell leukemia complicated by paraplegia. The patient initially responded to combination chemotherapy but succumbed to the disease two months after presentation.